Blue Amazon Management System (SisGAAz): Sovereignty, surveillance and defense of the Brazilian jurisdictional waters - Israel de Oliveira Andrade; Antonio Jorge Ramalho da Rocha; Luiz Gustavo Aversa Franco (Institute for Applied Economic Research (ipea), 2021)
Brazil is a country with a maritime vocation, whose development is intrinsically associated with the sea. The Brazilian coast and jurisdictional waters' extension constitute a challenge on themselves to the national defense. The presence of fundamental potentialities for the country, such as valuable natural resources, important urban centers and large population concentrations along the coast, and communication routes underline the importance of watching and protecting this area, called Blue Amazon. In order to provide adequate means to protect this large area, the Navy has developed strategic programs. One of these programs is the Blue Amazon Management System (SisGAAz), which currently goes through a reformulation due to the country's budgetary restraints. This study aims to demonstrate the importance of developing and implementing SisGAAz to monitor the Blue Amazon. It also discusses the implications of its reformulation, as well as the possible alternatives.
Keywords: L64; O32; O38; 330; national defense; science; technology and innovation; Brazilian Navy; Blue Amazon; sea power; public policy